1972
DOI: 10.1042/bj1290455
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and postnatal changes in the content and species of ferritin in rat liver

Abstract: The iron and ferritin content of rat liver and the species of ferritin present were examined from 4 days before to 3 weeks after birth. 1. Total iron and ferritin iron accumulated rapidly during the last days of gestation and from the second postnatal day underwent a steady depletion. 2. The amount of iron deposited before birth in the liver of each pup varied inversely with litter size and could be increased moderately by injection of iron into the mother before mating. 3. Intraperitoneal injection of iron 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
1

Year Published

1973
1973
1993
1993

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 23 publications
1
12
1
1
Order By: Relevance
“…Newborn rat liver is known as a storage organ for ferritin iron, with very high concentrations (Linder et al, 1972), and this is supported by our results. This may be due to the demand of erythrocytes accompanied with the rapid growth from birth to weaning.…”
Section: Discussionsupporting
confidence: 90%
“…Newborn rat liver is known as a storage organ for ferritin iron, with very high concentrations (Linder et al, 1972), and this is supported by our results. This may be due to the demand of erythrocytes accompanied with the rapid growth from birth to weaning.…”
Section: Discussionsupporting
confidence: 90%
“…If this hypothesis is correct, then under the influence of iron a subunit of the 'L' type which predominates in the more basic liver isoferritins may be synthesized at the expense of the 'H' type subunit characteristic of heart ferritin. The work of Linder et al (1972) lends support to this hypothesis, since they demonstrated that liver ferritin subunits in weanling rats differed from those of adult rat liver, but treatment with iron induced the formation of the adult liver ferritin type. The evidence of Konijn et al (1973) would indicate that the 'L' type subunits are those synthesized on free ribosomes.…”
Section: Discussionmentioning
confidence: 81%
“…For 12 of the dams, the stage of pregnancy was timed. In the case of nontimed dams, pup gestational age was determined by crown-to-rump length and weight, comparing values with those from the timed pups, as described previously (2). Rats were infused intravenously into the tail vein with 67Cu-labeled samples under light pentobarbital anesthesia ( I 5 mg/kg ip) and were sacrificed by exsanguination under heavy pentobarbital anesthesia (50 mg/kg), with heparin treatment (48).…”
Section: Methodsmentioning
confidence: 99%